The impact of consumer engagement towards consumer loyalty in tourism and hospitality industry - Leong, Mei Kei; Osman, Syuhaily; Paim, Laily (Malaysian Consumer and Family Economics (MACFEA), 2017)
Consumer loyalty is an important element in research for marketers to retain consumers regardless of industry. With the development of tourism and hospitality industry and the increasing popularity of social media, the engagement between the company and consumers is crucial to the success of the company. Additionally, the researchers’ increasing attention of consumer engagement and emergence as the predictor of loyalty has increased the need to study consumer engagement. The purpose of this study is to determine the relationships between the affective, behavioural, and cognitive dimensions of consumer engagement and consumer loyalty in the tourism and hospitality industry. In this study, there were 390 respondents that answered the survey through social media such as i.e., Facebook, Instagram and WeChat. The relationships between the variables were tested using SmartPLS 3.0 version, a software used to test the structural equation modelling. The findings of the study showed that the affective and behavioural dimensions of consumer engagement have a significant relationship on consumer loyalty. By referring to this relationship, it indicated that affective and behavioural engaged consumers might be more prone to be turned from engaged consumers to loyal consumers. The findings in this study are beneficial to marketers and consumers in understanding the consumer behaviour in the tourism and hospitality industry.